Women at work: Addressing the gaps - Carolina Robino; Raquel Tebaldi (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
Despite progress in education and health worldwide, women still face significant barriers to engage as full economic citizens. There are significant gender gaps in wages and labour market participation. In many cases, women also face barriers and lack the assets needed to become entrepreneurs. These inequalities remain large, persistent and pervasive in many parts of the world. Addressing these gaps is not only a moral imperative; there is growing evidence that gender equality can directly foster economic growth and broad-based social development.
Keywords: 330; Women; work; addressing; gaps